METABOLISMO NITROGENADO EM AVES ANTÁRTICAS: ATIVIDADE UREOGÊNICA E URICOGÊNICA DO FÍGADO E RIM DE Pygoscellis Papua - RODRIGUES, E.; CARVALHO, C.S.; BACILA, M. (Archives of Veterinary Science, 2003)
Foi levado a efeito uma pesquisa sobre metabolismo nitrogenado em pingüim Pygoscellis papua. A pesquisa foi centralizada no estudo da atividade ureogênica e uricogênica em fatias e homogenados bem como em frações subcelulares de fígado e de rim dessa ave antártica. Foi verificado que fígado e rim apresentam capacidade de uricogênese superior à ureogênese, fato esse que foi demonstrado pela determinação do conteúdo de uréia e de ácido úrico tanto em fatias como em homogenados de ambos os órgãos incubados em Ringer, contendo aspartato e glicina ou CO2; amônia, contendo aspartato e glicina ou CO2; glutamina e amônia, contendo aspartato e glicina ou CO2. Foi verificado ainda o efeito da L-ornitina e da amônia na etapa mitocondrial da síntese da uréia. Nitrogen metabolism in antarctic birds: ureogenic and uricogenic activity from the liver and kidney of Pygoscellis papua Abstract A research has been carried out on the nitrogen metabolism in the penguin Pygoscellis papua. This study has been centered on the ureogenic and uricogenic activities of slices and homogenates as well as in subcellular fractions from the liver and kidney of this Antarctic bird. It has been found that both liver and kidney display an uricogenic activity higher than that one of the ureogenesis. This fact has been demonstrated by the assay of urea and uric acid in both slices and homogenates from both organs incubated in systems containing Ringer solution and aspartate and glycine or CO2; ammonia with L-aspartate and glycine or CO2; glutamine and ammonia with L-aspartate and glycine or CO2. A research has been carried out also on the effect of L-ornithine and ammonia, on the mitochondrial step of the urea synthesis.